Mongolia : Technical Assistance Report-High Frequency Indicators Mission. - International Monetary Fund. Statistics Dept.. (Washington, D.C. : International Monetary Fund, 2022)
The IMF conducted a remote technical assistance (TA) mission from March 1 to 12, 2021, to help the National Statistics Office of Mongolia (NSOM) compile a monthly indicator of economic activity (MIEA). Experimental results describe monthly economic activity from January 2010 to January 2021 as well as the impact of the COVID-19. This second mission for developing the MIEA was funded by the IMF's Data for Decisions trust fund1 (D4D).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Mongolia